PEMANFAATAN IACI UNTUK MENGGALI POTENSI DIRI DAN MEMOTIVASI SISWA DI SMA MASEHI BERASTAGI. - Sitepu, Christina; Depari, Victory; Zebua, Intan; Sirait, Jelita Sirait (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2024)
The IACI (Ice Breaking, Atmospheric, Creative and Innovative) approach has become the main focus in improving the quality of learning in secondary schools through Community Service (PkM) activities. This activity aims to explore the implementation of IACI at Mesehi Berastagi High School and analyze its impact on student participation, student responses, learning activities, development of personal potential, and learning motivation. The research method used is a case study using observation, interviews and document analysis as data collection techniques. The results of the activities show that the implementation of the IACI approach at Mesehi Berastagi High School has had a positive impact. The increase in student participation in learning activities reached 85%, while positive student responses to the IACI approach reached 90%. More interactive and creative learning activities contribute 75% to student skill development. The development of students' personal potential looks significant with a percentage of 80%, while the increase in students' motivation in learning reaches 88%. The discussion of the results shows that active student participation, positive responses, interactive learning activities, development of personal potential, and increased student motivation are indicators of the effectiveness of implementing IACI at SMA Mesehi Berastagi. A comfortable learning atmosphere, creative and innovative activities are key factors in achieving positive results. The implication of this research is the importance of continuing to encourage the implementation of the IACI approach in schools as an effort to improve the quality of learning and develop students' potential holistically.